Peer Feedback Technique in Teaching Writing Skill of the Third Semester Students of IAIN Parepare - Magdahalena Magdahalena; Rasmah Nursira (EDUVELOP, 2018)
Writing is still considered as a difficult skill in language learning by Indonesian students. For that reason, it is urgent for teacher to seek for interesting ways to teach writing in the classroom. This study examines the effectiveness of the use of peer feedback technique to improve students’ skill in writing descriptive paragraph. Some studies have proved the effectiveness of the technique to improve students’ writing skill. The study employs experimental research in which one class of 20 students is taught to write narrative paragraph and correct their paragraph using peer feedback technique. The result of the study shows that the technique improves the students writing skill in narrative writing, however the scores are not significant. This suggests that there is a factor that affects the result of the teaching using peer feedback, and it is the less time of treatment which is indicated as the factor.